Marriage Dispensation and Gender Justice from a Mubādalah Perspective: A Critical Analysis of Tanjungkarang Religious Court Decision No. 131/Pdt.P/2024/PA.Tnk - Husain Fadhil Arrasyid; Hervin Yoki Pradikta (Brajamusti Publication, 2025)
This article critically examines issues of gender justice in marriage dispensation cases through an in-depth analysis of the Tanjungkarang Religious Court Decision No. 131/Pdt.P/2024/PA.Tnk. The petition for marriage dispensation was rejected on procedural grounds due to the petitioners’ absence, despite the urgent circumstances involving an underage girl who was pregnant. This study seeks to assess whether the judicial reasoning and outcome reflect substantive justice and provide adequate legal protection for vulnerable female parties. Employing a normative juridical approach and drawing on the reciprocity (Mubādalah) theory developed by Faqihuddin Abdul Kodir, the decision is analyzed both textually and contextually. The findings indicate that the legal reasoning remains predominantly procedural and insufficiently responsive to women’s lived experiences, thereby marginalizing their position as legal subjects. The reciprocity perspective offers an ethical and jurisprudential alternative that repositions women as active, equal, and reciprocal participants in legal relationships. This research contributes to the advancement of a more just, inclusive, and socially responsive framework of Islamic family law and advocates for the incorporation of reciprocity principles into judicial practice to enhance gender-sensitive adjudication.